Influence of menstrual phase and symptoms on sleep before and after matches for professional footballers - Brown, G. A.; Fullagar, H. H. K.; Duffield, R. (Scandinavian Journal of Medicine & Science in Sports, 2025)
This study investigated the association of menstrual cycle phase and symptoms with objective and subjective sleep measures from professional footballers before and after matches. Twenty-three non-hormonal contraceptive-using professional footballers (from four clubs) were monitored for up to four menstrual cycles during a domestic league season. Menstrual phases (menstruation, mid-late follicular, luteal) were determined using calendar counting and urinary hormone tests (luteinizing hormone and pregnandiol-3-glucuronide). Players rated the severity of 18 symptoms on the evenings of matches and the following two evenings. Individual daily summed menstrual symptom severity (MSS) scores were calculated. Subjective sleep quality was rated the morning of matches and the following two mornings. Objective sleep (bedtime, waketime, total sleep time [TST], sleep onset latency, wake after sleep onset, sleep efficiency) obtained from actigraphy was measured the night prior to (MN-1), of (MN), and following (MN+1) matches. Linear mixed models were performed for each sleep measure to examine the effects of menstrual phase and symptoms. Bedtime was significantly later for MN (p < 0.001), waketime was significantly earlier for MN+1 (p < 0.001), and TST was significantly longer for MN-1 (p < 0.001). Menstrual phase did not have a significant effect on any sleep variable (p > 0.05). Increased MSS score was associated with increased TST (p = 0.03) and increased waketime (p = 0.03). Increased lower back pain severity and mood changes/anxiety severity were associated with increased waketime (p = 0.048) and TST (p = 0.009), respectively. Overall, bedtime and waketime were affected by the night related to matches, with increased TST the night before a match. Menstrual phase was not related to any objective or subjective sleep variables, whilst increasing menstrual symptom severity was related to later waketime and longer TST.